Analysis of Structural Solutions for Radiators in Buildings - Bargłowski, Leszek; Adamski, Mariusz; Rebman, Maksym (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the following article emphasizes the analysis of technical and economic criteria for radiators, that will help you make the right choice of radiator type. Different solutions for heating flats are presented, the focus is on water-fed radiator solutions. After detailed analysis, the evaluation criteria are selected: indicators of the unit heat output of a radiator related to the mass, volume and length of the radiator QM, QV, QL. Radiator types, nominal working parameters, evaluations criteria and techno-economic analysis of structural solutions for radiators on the example of a residential building are presented.
Keywords: radiator; central heating system; indicators of the unit heat output of a radiator; technical assessment; economic assessment; hygiene criteria; evaluation